Pengembangan Website Edukasi Kesehatan Balita dengan Menggunakan Metode Iterative Incremental - Abidzar Zulfa Arifa Kusyono; Taufik Nur Adi; Elvira Lailatuth Thohiroh (STMIK Budi Darma, 2024)
This study aims to develop a health education website for toddlers in Indonesia that provides relevant and comprehensive information to the community, especially parents. The study identifies issues in providing toddler health information and designs a website that facilitates access to this information. It also explores the technologies and methods needed for developing the website. The research methodology includes the Information Systems (IS) environment, which is divided into actors, organizations, and technology, as well as theories encompassing UML concepts, Laravel, and PHP. An Iterative Incremental approach is used for website development, including stages such as initial planning, planning, requirement, analysis and design, implementation, testing, and deployment. Testing is conducted using the Black Box Testing method. Data collection is carried out through literature studies, online surveys, and interviews with parents and health science students. Literature studies help build the theoretical foundation, provide current data, and identify best practices. Online surveys measure user needs and community awareness regarding toddler health issues, while interviews delve into user preferences and behaviors. The results show that the development of the toddler health education website in Indonesia successfully provides complete and relevant information, facilitating easy access for parents. The implementation using the Laravel framework and PHP programming language, along with testing using the Black Box Testing method, proved effective. Iterative evaluation improved the website's functionality based on user feedback. This study significantly contributes to the development of toddler health education media that meets the needs of the Indonesian community.